Laparoscopic distal pancreatectomy for metastatic melanoma originating from the choroidal membrane: a case report - Shigeaki Baba; Yuji Akiyama; Fumitaka Endo; Haruka Nikai; Ryo Sugimoto; Akira Umemura; Hirokatsu Katagiri; Yasushi Hasegawa; Takeshi Iwaya; Hiroyuki Nitta; Keisuke Koeda; Tamotsu Sugai; et al. (Surgical Case Reports)
Abstract Background Metastatic melanoma originating from the choroidal membrane is extremely rare. Here, we report a case of laparoscopic distal pancreatectomy for malignant melanoma that developed after heavy-particle therapy for malignant choroidal melanoma. Case presentation A 43-year-old Japanese woman underwent 70 Gy heavy-particle radiotherapy for a right choroidal malignant melanoma. Positron emission tomography-computed tomography examination was performed 4 years after treatment, when contrast accumulation was observed on the posterior wall of the stomach. Endoscopic ultrasonography and computed tomography showed a mass with contrast enhancement in contact with the stomach wall. Based on the imaging findings, a gastrointestinal stromal tumor of the posterior wall of the lower gastric corpus with extramural growth was suspected. Laparoscopic surgery was performed under general anesthesia. A black-pigmented tumor originating from the pancreas was discovered. Following an intraoperative diagnosis of metastasis of malignant melanoma, a laparoscopic distal pancreatectomy was performed. The pathological diagnosis was pancreatic metastasis of malignant melanoma. The patient was treated with adjuvant immune checkpoint inhibitors and chemotherapy after surgery, which led to long-term survival. Conclusions Including this case, only eight case reports on pancreatic resection for metastatic ocular malignant melanoma have been reported. The ocular malignant melanoma with distant metastasis has a poor prognosis. Therefore, in our case, careful follow-up is required. A single pancreatic metastasis from a malignant melanoma of the choroid can be successfully managed by laparoscopic radical resection of the pancreas, and molecularly targeted adjuvant chemotherapy.